2016
DOI: 10.18203/2394-6040.ijcmph20163059
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cervical cancer during pregnancy

Abstract: INTRODUCTIONCervical cancer is one of the most common malignancy among females, worldwide.1 Every year, more than 493,000 individuals are diagnosed with and 274,000 die from cervical cancer. The majority of these cases (80%) are experienced in developing countries.2 PAP smear is the most sensitive and specific screening test for cervical cancer in reducing mortality and morbidity of women. However, high incidence and mortality rates continue in developing countries due to the lack of screening programmes. 4 In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 5 publications
2
14
1
Order By: Relevance
“…This is in contrast to study results conducted at Coimbatore by Manikkam, where 80% of women and Turkish studies showed that 60.7% women were aware of Pap smear. 3,11 This difference may be due to difference in population characteristics under study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to study results conducted at Coimbatore by Manikkam, where 80% of women and Turkish studies showed that 60.7% women were aware of Pap smear. 3,11 This difference may be due to difference in population characteristics under study.…”
Section: Discussionmentioning
confidence: 99%
“…2 This also provides an opportunity to educate and create awareness about cancer cervix and motivate them for future regular Pap smear screening for themselves and members of her community. 11 In addition, Pap smear also gives information about genital infections such as bacteria, fungus, virus etc. This provides an opportunity to detect asymptomatic genital infections and there by treat it, which otherwise could have an adverse effect on ongoing pregnancy outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy is a potential opportunity to counsel and educate pregnant women regarding the significance of Pap smear (Manikkam, 2016). Studies have confirmed that Pap smear test is safely done during pregnancy irrespective of gestational age (Botha and Dreyer, 2017;Heena et al, 2019;Manikkam, 2016). Progressively, several studies have confirmed positive intraepithelial lesions detected during pregnancy (Ncube et al, 2019, Manikkam, 2016.…”
Section: Perceptions Of Midwives On Pap Smear Tests During Pregnancymentioning
confidence: 99%
“…This is to avoid missed opportunities among pregnant women (DoH, 2017). Pregnancy is a potential opportunity to counsel and educate pregnant women regarding the significance of Pap smear (Manikkam, 2016). Studies have confirmed that Pap smear test is safely done during pregnancy irrespective of gestational age (Botha and Dreyer, 2017;Heena et al, 2019;Manikkam, 2016).…”
Section: Perceptions Of Midwives On Pap Smear Tests During Pregnancymentioning
confidence: 99%